PENYELESAIAN KREDIT BERMASALAH PROGRAM KUR PADA PT BRI (Persero) UNIT CITRA NIAGA - -, Rien Novianda (EKONOMIA, 2014)
The study was conducted to resolve problem loans that must be completed by the bank as early as possible by using the basic theory of finance, Non Perfoming Loan (NPL) and the Loan to Deposit Ratio (LDR).The data was collected using field research. Processed based on financial analysis Unit Citra Niaga PT Bank Rakyat Indonesia (Persero) Tbk consisting of balance sheet, income statement, statement deptor position and Kupede rekapitulation outstanding (Periode 2009,2010,2011).The results of the analysis and discussion ofÂ researsch Non Perfoming Loan (NPL), Loan to Deposit Ratio (LDR) increased company perfomance. Espesially from a decline Non Perfoming Loan (NPL) of 57.74% and Loan to Deposit Ratio (LDR) continues to increase from year to year. Means that the handling problem loans can be resolved properly. And Loan to Deposit Ratio (LDR) prove that the soundness of the deposit of the debtor be seen very well.